The effect of training, mentality and entrepreneurship on business success for employee pensions - Sinaga, Ferry; Suryadi, Suryadi; Akbar, Ma'ruf (Archives of Business Research, 2019)
This study aims to analyze (1) the direct effect of training on business success for prospective retirees; (2) the direct effect of mentality on business success for prospective retirees; (3) the direct effect of entrepreneurship on business success for prospective retirees; (4) the direct effect of training on entrepreneurship for retirement candidates PT. Bank BNI; (5) the direct effect of mentality on entrepreneurship for prospective retirees; and (6) the direct effect of training on the mentality of prospective retirees. The population in this study was retired PT. BNI banks in the Indonesian region that attended pre-retirement training at the time of retirement (aged 50-55 years) was 264 people. The sampling technique using Slovin formula obtained as many as 160 respondents. The results of the study indicate that (1) the training implemented has been actualized to retired PT. Bank BNI employees to realize the success of the business that will be undertaken. The training was in the form of pre-retirement given to every retired PT. Bank BNI as a provision for entrepreneurship in retirement; (2) retired employees are mentally prepared to pursue business in realizing business success. This mentality is needed as the stability of the soul and personality to run the business to be successful; (3) retired employees carry out entrepreneurship to realize business success. Entrepreneurial desire is the main motive for realizing the success of the business he is engaged in; (4) provide continuous training to retired employees to prepare them for entrepreneurship. The results of the pre-retirement training that were followed provided benefits for running entrepreneurship; (5) every retired employee is ready to carry out the entrepreneurial mentality he is practicing. Mental readiness to dare to make entrepreneurial decisions in retirement; and (6) retired employees who attend training mentally are ready to face the retirement period with entrepreneurship. Training before retirement has led to the realization of a persistent mentality in entrepreneurship.